Efektivitas Manajemen Operasional Penyelenggaraan Ibadah Haji di Era Digital - Kamaruddin (Institut Agama Islam Syubbanul Wathon Magelang, 2026)
This study aims to evaluate the effectiveness of operational management in the administration of the Hajj in the digital age, characterized by the use of integrated information systems and technology-driven service transformation. The study focuses on the use of Hajj digitization through the SISKOHAT and SISKOPATUH systems, as well as the integration of cross-border services to support the smooth administration of the Hajj. To what extent technology contributes to improving service quality is examined in this study through policy analysis. The research indicates that digitalization can enhance service speed, accuracy, transparency, and the effectiveness of real-time oversight. However, digitalization still faces numerous challenges. Some of these include low digital literacy among members of the public, limited human resources, and the need to balance technological advancements with a human-centered approach to service delivery. Therefore, for Hajj digitalization to operate optimally and sustainably, plans are needed to enhance human resource capacity and develop inclusive systems.